IMPLEMENTATION OF FINGER PAINTING BASED ON ISLAMIC WEBSITES IN IMPROVING ISLAMIC IDENTITY IN EARLY CHILDHOOD - Sri Windari; Masganti Sit; Sapri Sapri (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
Islamic identity is very important to be instilled from an early age in children, various approaches to children are presented so that children can be accepted well and attached to themselves. The fundamental thing is to start with optimal stimulation for cognitive and motor. Therefore, the purpose of this study is for educators to be able to implement Islamic identity in children through the presentation of pictures of historical sites in the world by applying finger painting activities. In Al Washliyah Klambir Lima IT Kindergarten, learning is carried out in an interesting and fun method, where schools with Islamic education content always strive to instill Islamic values in their students to realize an Islamic generation with character. This study uses descriptive qualitative methods and data analysis using the Miles and Huberman model where data reduction, data presentation, and conclusion drawing are the main techniques by describing systemically a certain field related to the situation in the learning process carried out at Al Washliyah Klambir Lima IT Kindergarten. The development of children's Islamic identity in Al Washliyah Klambir Lima IT Kindergarten shows that children have changed, both in skills and religious knowledge, where children can show better than before in terms of Islamic insight so that they can look exemplary and have a good personality.